2014
DOI: 10.1115/1.4026609
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Model for Prediction of Bubble Growth at Nucleation Site in Microchannels

Abstract: Formation of the first bubble at nucieation site is an inception of the two phase flow in pool boiling and flow boiling. Bubble dynamics (bubble nucieation, growth, and departure) plays an important role in heat transfer and pressure drop characteristics during rv,'o phase flow in microchanneis. In this paper, a simplified model has been developed for predicting bubble growth rate at nucieation cavity in microchannel. It is assumed that heat supplied at nucieation site is divided between the liquid phase and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Among them, Barber J et al [10] found through experimental research that fluid velocity, pressure and channel size are important parameters affecting cavitation phenomenon in microchannels. In addition, Kadam S T [11] used numerical simulation methods to analyze in detail the flow characteristics of bubble formation, growth and shedding in microchannels, providing important clues for further understanding of the mechanism of cavitation in microchannels.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Barber J et al [10] found through experimental research that fluid velocity, pressure and channel size are important parameters affecting cavitation phenomenon in microchannels. In addition, Kadam S T [11] used numerical simulation methods to analyze in detail the flow characteristics of bubble formation, growth and shedding in microchannels, providing important clues for further understanding of the mechanism of cavitation in microchannels.…”
Section: Introductionmentioning
confidence: 99%